Correlation of Postoperative Pain to Quality of Recovery in the Immediate Postoperative Period. Issue 6 (1st November 2005) - Wu, Christopher L.; Rowlingson, Andrew J.; Partin, Alan W.; Kalish, Murray A.; Courpas, Genevieve E.; Walsh, Patrick C.; Fleisher, Lee A.
Abstract : Background and Objectives: It is unclear whether the severity of postoperative pain may affect patients' quality of recovery in the immediate postoperative period (within 2 weeks of surgery). Methods: This was a prospective, observational study in patients undergoing elective radical retropubic prostatectomy. All patients received a standardized intraoperative general or spinal anesthetic followed by intravenous patient-controlled analgesia. Visual analog scores for pain at rest, pain with activity, and nausea along with the QoR, an instrument validated to assess quality of recovery in the postoperative period, and Brief Fatigue Inventory were assessed on postoperative days 1 to 3, 7, and 30. The Epworth Sleepiness Scale was assessed on postoperative days 7 and 30. Results: We found that the severity of pain both at rest and with activity correlated with a decrease in quality of recovery as assessed by the QoR. Conclusions: Our findings suggest that an increase in postoperative pain is correlated with a decrease in a patient's quality of recovery in the immediate postoperative period.